INTEGRATING CLIMATE CHANGE NARRATIVES IN PRIMARY EDUCATION: A PICTURE BOOK APPROACH - Arya Muhaimin; Sary Silvhiany; Rita Inderawati (University of Kuningan, 2026)
This study investigated how children's literature can be utilized effectively to integrate climate change education into English Language Teaching (ELT) for young learners, specifically fifth graders at SDN 115 Palembang. Using two locally relevant environmental picture books, My Clay Batik and Protecting the Palace, the researcher conducted three teaching sessions combining language skills development with environmental awareness. Data were collected from classroom observations, student worksheets, surveys, and interviews. Results showed that the use of these picture books made complex climate change concepts accessible and engaging, enhancing students’ understanding of environmental issues such as pollution and deforestation. The storytelling approach fostered active student participation, increased interest in environmental topics, and encouraged eco-friendly attitudes and behaviors outside the classroom. The study concludes that integrating climate change themes into ELT not only supports language acquisition but also promotes environmental responsibility.